2023
DOI: 10.1002/ecy.4049
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus scarcity contributes to nitrogen limitation in lowland tropical rainforests

Abstract: There is increasing evidence to suggest that soil nutrient availability can limit the carbon sink capacity of forests, a particularly relevant issue considering today's changing climate. This question is especially important in the tropics, where most part of the Earth's plant biomass is stored. To assess whether tropical forest growth is limited by soil nutrients and to explore N and P limitations, we analyzed stem growth and foliar elemental composition of the five stem widest trees per plot at two sites in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 79 publications
1
3
0
Order By: Relevance
“…The responses of foliar nutrients to nutrient additions were species-specific and considerably variable (Extended Data Table 6), posing a challenge to drawing meaningful conclusion on nutrient limitation status of the overall ecosystem, as espoused by others 36 . Generally, foliar N of pooled dominant species increased with N and P additions, similar to observations in French Guiana 35 . Nitrogen addition increased foliar N in Celtis mildbraedii whereas P addition increased foliar P in Celtis durandii, consistent with other studies 51,52 , except for absence of K addition effect on foliar K. These highlight that leaf growth, biochemical traits and senescence of different species may be limited by different nutrients.…”
Section: Foliar Nutrient Responses To Nutrient Additionssupporting
confidence: 85%
See 1 more Smart Citation
“…The responses of foliar nutrients to nutrient additions were species-specific and considerably variable (Extended Data Table 6), posing a challenge to drawing meaningful conclusion on nutrient limitation status of the overall ecosystem, as espoused by others 36 . Generally, foliar N of pooled dominant species increased with N and P additions, similar to observations in French Guiana 35 . Nitrogen addition increased foliar N in Celtis mildbraedii whereas P addition increased foliar P in Celtis durandii, consistent with other studies 51,52 , except for absence of K addition effect on foliar K. These highlight that leaf growth, biochemical traits and senescence of different species may be limited by different nutrients.…”
Section: Foliar Nutrient Responses To Nutrient Additionssupporting
confidence: 85%
“…The current most-limiting nutrients to Afrotropical forest productivity and how they may change in the future remain open questions. Whereas P (co-)limitation is common in neotropical forests 12,15,35 , experimental evidence of P-limited productivity in Afrotropical forests is yet to be reported. A recent meta-analysis involving 48 nutrient manipulation experiments (NME) in tropical forests 12 included neotropics (32), South-East Asia (8) and Hawaii (8), but not Afrotropical forests.…”
Section: Nutrient-limited Leaf Litterfall Linked To Seasonal Droughtmentioning
confidence: 99%
“…The trade-off between maintaining soil P storage and improving plant productivity, therefore, has become one of the important drivers for inspiring global political disputes in recent years (Barbieri et al 2021;Langhans et al 2021;Tonini et al 2019;Withers 2019). Among them, exploring plant P utilization strategies (Turner et al 2018;Vallicrosa et al 2023;Yu et al 2022), clarifying the fate and patterns of releasing P from litter (Strukelj et al 2017;Tie et al 2023), and elucidating soil P-fractions and their transformation processes (Brandtberg et al 2010;Liu et al 2021;Vincent et al 2013) are the fundamental scientific questions.…”
Section: Introductionmentioning
confidence: 99%
“…However, these forests are often associated with P limitation due to strong soil weathering (Tie et al 2023;Yang et al 2021). In addition, the subtropical and tropical forests grow fast and have high net primary productivity, thus P can be taken up from soil and transported to plants (e.g., leaves, trunks, roots) quickly, which potentially results in a loss of soil P and thus reduced soil P concentration (Peñuelas et al 2011;Vallicrosa et al 2023). For example, prior studies reported that soil total P concentration and its availability decreased with stand development across tropical and subtropical forests (Huang et al 2013;Izquierdo et al 2013;Selmants and Hart 2010).…”
Section: Introductionmentioning
confidence: 99%